NMR T1–T2 correlation analysis of molecular absorption inside a hardened cement paste containing silanised silica fume. (18th April 2019) - Cadar, Calin; Cretu, Andrea; Moldovan, Marioara; Mattea, Carlos; Stapf, Siegfried; Ardelean, Ioan
ABSTRACT: The influence of silanised silica fume addition on the pore size distribution and wettability of white cement paste was investigated using T1 –T2 correlation nuclear magnetic resonance (NMR) relaxometry. Surface silanisation of silica fume particles was achieved by the hydrolysis reaction of APTES (3-Aminopropyltriethoxysilane) and condensation of the silanol functional groups on the surface. The methods used for characterisation of the silanised silica fume particles were scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR) and thermogravimetric analysis (TGA). By adding silanised silica fume to the cement paste, the accessibility of water molecules to the porous system becomes restricted, leading to a lower permeability in comparison with the unmodified cement paste. Differential scanning calorimetry (DSC) measurements on the cement pastes saturated with Octamethylcyclotetrasiloxane confirm also that the size of inter-C–S–H and capillary pores is not influenced by the addition of silica fume in a detectable manner. GRAPHICAL ABSTRACT: